Migratory insertion of [B(C6F5)2] into C-H bonds: CO promoted transfer of the boryl fragment. - Aldridge, S; Kays, D; Al-Fawaz, A; Jones, K; Horton, P; Hursthouse, M; Harrington, R; Clegg, W (2006)
The reaction of (eta(5)-C5H5)Fe(CO)2B(C6F5)2 with CO has been shown to proceed via ligand substitution at the metal with accompanying transfer of the boryl fragment (via C-H insertion) to the Cp ring, thereby generating the zwitterion [eta(5)-C5H4B(C6F5)2H]Fe(CO)3 in quantitative yield.